2008
DOI: 10.1007/s00421-008-0880-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of recreational physical activity with homocysteine, folate and lipid markers in young women

Abstract: We assessed the influence of recreational physical activity in young healthy women on homocysteine, a potential risk factor for cardiovascular disease (CVD). Participants were 124 23-year-old normal-weight Italian recreational athletes (performing 8.7 +/- 2.46 h week(-1) exercise) and 116 controls. Median blood homocysteine, folate and lipid markers did not differ between athletes and controls. Elevated homocysteine levels at CVD risk > or =12.0 and > or =15.0 micromol l(-1) were not different between groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
1
19
0
2
Order By: Relevance
“…This might be indicating a change of dietary status. However; the folic acid level is declared as the main factor that can affect Hcy metabolism in great number of the researches [11,[15][16][17]19,21,23]. Our results supported these findings.…”
Section: Maximum Aerobic Capacitysupporting
confidence: 86%
See 2 more Smart Citations
“…This might be indicating a change of dietary status. However; the folic acid level is declared as the main factor that can affect Hcy metabolism in great number of the researches [11,[15][16][17]19,21,23]. Our results supported these findings.…”
Section: Maximum Aerobic Capacitysupporting
confidence: 86%
“…It was thought that the alterations of the creatine synthesis might change the Hcy levels due to formation of S-adenosylhomocysteine (the precursor of Hcy) from S-adenosylmethionine enhanced by high creatine synthesis [11]. Further; physical activity influences plasma protein metabolism and turnover and the concentration of amino acids such as methionine [1,16]. An increase in methyl group turnover increases Hcy production.…”
Section: Maximum Aerobic Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Diets abundant in vegetables, fruits and bread can result in reduction in the PHcy. [15] Elevated levels of Homocysteine (eHcy or hyperhomocysteinaemia) occur with aging and decreased renal function. [14][15][16][17] Our study has observed a strong link between hyperhomocysteinaemia and ischaemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Elevated levels of Homocysteine (eHcy or hyperhomocysteinaemia) occur with aging and decreased renal function. [14][15][16][17] Our study has observed a strong link between hyperhomocysteinaemia and ischaemic stroke. The findings are supported by recent study, which showed that hyperhomocysteinaemia was found in 48% of ischaemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%